2022
DOI: 10.3390/nu14235118
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment Mediates the Association between Dietary Inflammation and Depressive Symptoms in the Elderly

Abstract: The underlying mechanism in both cognitive impairment and depression was chronic inflammation, which could be reflected by the dietary inflammatory index (DII). However, the effect of cognitive impairment on the association between DII and depression was not clear. Therefore, in this study, we hypothesized that cognitive impairment could mediate the association between dietary inflammation and depressive symptoms. A total of 2550 participants aged ≥60 from the National Health and Nutrition Examination Survey (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In addition, our findings also indicate that middle-aged and older people with hypertension, diabetes, or arthritis who also suffer from depressive symptoms are at a higher risk of mortality. Numerous studies have already demonstrated the association between depressive symptoms and cardiovascular diseases, diabetes, chronic inflammation, and immune system disorders ( 113 116 ). These cross-sectional studies have indicated that depressive symptoms exacerbate the condition of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our findings also indicate that middle-aged and older people with hypertension, diabetes, or arthritis who also suffer from depressive symptoms are at a higher risk of mortality. Numerous studies have already demonstrated the association between depressive symptoms and cardiovascular diseases, diabetes, chronic inflammation, and immune system disorders ( 113 116 ). These cross-sectional studies have indicated that depressive symptoms exacerbate the condition of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Language uency is rated based on the number of animals named [55]. Participants' working memory, processing speed, and sustained attention are gauged within two minutes using the Digital Symbol Substitution Test (DSST), requiring them to accurately replicate symbols from a grid of 133 boxes [56,57].…”
Section: Outcome Variablesmentioning
confidence: 99%